Microbiological hazard associated with using of mobile phones in hospital clinical laboratories from Maracaibo-Venezuela - América Paz-Montes; Alisbeth Fuenmayor-Boscán; Lisette Sandrea; Joelymar Colmenares; Milagros Marín; Egleé Rodríguez (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2015)
The use of mobile phones is widespread in health institutions, including areas with defined microbiological risk as clinical laboratories. In this study, the presence of potentially pathogenic bacteria was investigated in mobile phones of laboratory personnel of four hospitals of Maracaibo, Venezuela. Qualitative microbiological culture of swabs from the surface of 200 mobile phones was performed. A questionnaire was applied, to evaluate adherence of staff to standard hygiene practices during the workday. In 83% of phones bacterial contamination was evidenced, and 29% had bacteria with defined pathogenic potential, predominantly Enterococcus spp., strict anaerobes bacteria, Staphylococcus aureus and enterobacteria. Some pathogenic strains showed resistance patterns suggestive of nosocomial bacteria. A high percentage of staff refused to apply minimal hygiene measures to manipulate their phones during the workday. Microbiological results, analyzed together with the low level of adherence of personnel to the standard hygienic practices, allow attributing an important hazard to mobiles phone use in clinical laboratories, which could involve not only owners of such devices and usual manipulators, but also could extend to his occasional manipulators in the community.